Synthetic Ontology: Polyphase Stages of the Techno-Capitalist Being - Rodríguez Ortiz, Roxana (2023)
In this text, I develop three categories or polyphasic stages of being, that account for the synthetic ontology understood as the timeless juxtaposition of diverse scopes of being at different moments of the use of technology in the history of humanity, in the conformation of techno-capitalism and philosophical thought. I call these stages mecanólogo, technólogo, and organólogo. For this, I develop a methodology that allows me to cross various aspects of analysis and exemplify in our context each one of these polyphasic stages of being, starting mainly from the notion of individuation of Simondon.